Search for light sterile neutrinos with the T2K far detector Super-Kamiokande at a baseline of 295km - Abe, K; Akutsu, R; Ali, A; Andreopoulos, C; Anthony, L; Antonova, M; Aoki, S; Ariga, A; Ashida, Y; Awataguchi, Y; Azuma, Y; Ban, S; et al. (American Physical Society, 2019)
We perform a search for light sterile neutrinos using the data from the T2K far detector at a baseline of 295 km, with an exposure of 14.7(7.6)×10^20 protons on target in neutrino (antineutrino) mode. A selection of neutral-current interaction samples is also used to enhance the sensitivity to sterile mixing. No evidence of sterile neutrino mixing in the 3+1 model was found from a simultaneous fit to the charged-current muon, electron and neutral-current neutrino samples. We set the most stringent limit on the sterile oscillation amplitude sin^2θ24 for the sterile neutrino mass splitting Δm^2v41<3×10^−3eV^2/c^4.